Incidence and prognostic impact of KRAS and BRAF mutation in patients undergoing liver surgery for colorectal metastases. Issue 23 (19th September 2013) - Karagkounis, Georgios; Torbenson, Michael S.; Daniel, Hubert D.; Azad, Nilofer S.; Diaz, Luis A.; Donehower, Ross C.; Hirose, Kenzo; Ahuja, Nita; Pawlik, Timothy M.; Choti, Michael A.
<x xml:space="preserve">Abstract</x> BACKGROUND Molecular biomarkers offer the potential for refining prognostic determinants in patients undergoing cancer surgery. Among patients with colorectal cancer, KRAS and BRAF are important biomarkers, but their role in patients undergoing surgical therapy for liver metastases is unknown. In this study, the incidence and prognostic significance of KRAS and BRAF mutations were determined in patients undergoing surgical therapy of colorectal liver metastases (CRLM). METHODS KRAS and BRAF analysis was performed on 202 patients undergoing surgery for CRLM between 2003 and 2008. Tumor samples were analyzed for somatic mutations using sequencing analysis (KRAS, codon12/13, BRAF, V600E). The frequency of mutations was ascertained, and their impact on outcome was determined relative to other clinicopathologic factors. RESULTS KRAS gene mutations were detected in 58/202 patients (29%). In contrast, mutation in the BRAF gene was identified in very low frequency in this surgical cohort, found in only 4/202 (2%) patients. On multivariate analysis, KRAS mutation was associated with worse survival (hazard ratio [HR], 1.99; 95% confidence interval [CI], 1.21‐3.26), as well as recurrence risk (HR, 1.68; 95% CI, 1.04‐2.70). Although other clinicopathologic features, including tumor number, carcinoembryonic antigen, and primary stage were also associated with survival, KRAS status remained independently predictive of outcome. The low incidence of BRAF mutation limited assessment of its prognostic impact. CONCLUSION Whereas KRAS mutations were found in approximately one third of patients, BFAF mutations were found in only 2% of patients undergoing surgery for CRLM. KRAS status was an independent predictor of overall and recurrence‐free survival. Molecular biomarkers such as KRAS may help to refine our prognostic assessment of patients undergoing surgical therapy for CRLM. Cancer 2013;119:4137–4144. ©2013 American Cancer Society.